Information Disclosure and Control on Online Social Network Sites among Medical Undergraduates (Medico Legal Update, 2021)
Introduction: Internet usage has become a big part of many people’s lives, and among the many uses SocialNetworking Sites (SNS) which became very prevalent. How privacy concerns, trust and control are affectingSNS usage and self-disclosure has become an important question for many people.Aim: Aim of the study is to assess the information disclosure and control on online social network sitesamong medical undergraduates.Methodology: The study was conducted at Saveetha medical college and hospital among medicalundergraduates. A questionnaire on usage of online social networks and information disclosures wasadministered and analysed it for reliability, social network site usage, privacy concerns, and disclosure ofautobiographical memories.Result: Almost 81.1% of the people feel that their browsing history were tracked by social networking sites.Instagram is mainly used app by medical undergraduates (40%).Conclusion: There is an excess usage of social networking sites and easy information disclosure is seen inthe population.